Self-Healing Materials Systems: Overview of Major Approaches and Recent Developed Technologies - B. Aïssa; D. Therriault; E. Haddad; W. Jamroz (Advances in Materials Science and Engineering)
The development of self-healing materials is now being considered for real engineering applications. Over the past few decades, there has been a huge interest in materials that can self-heal, as this property can increase materials lifetime, reduce replacement costs, and improve product safety. Self-healing systems can be made from a variety of polymers and metallic materials. This paper reviews the main technologies currently being developed, particularly on the thermosetting composite polymeric systems. An overview of various self-healing concepts over the past decade is then presented. Finally, a perspective on future self-healing approaches using this biomimetic technique is offered. The intention is to stimulate debate and reinforce the importance of a multidisciplinary approach in this exciting field.